2017
DOI: 10.7901/2169-3358-2017.1.457
|View full text |Cite
|
Sign up to set email alerts
|

To Remove or Not to Remove? Dealing with pollution risks from ship wrecks

Abstract: (ID: 2017-155) ABSTRACT The navigational and environmental risks posed by ship wrecks have presented a challenge to governments and the maritime industry for decades. In more recent years a consensus has developed worldwide based on assessing these risks and undertaking measures proportional to the severity of those risks. This approach has been formalised in the Nairobi International Convention on the Removal of Wrecks 2007. With recent developments in salvage technology and equi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Consoli et al (2015) reported that oil pollution is commonly resulted due to maritime accidents that significantly impacting marine environment and often portrayed by the media as environmental disasters with dire consequences predicted for the survival of marine flora and fauna, which therefore, mandatory for appropriate remediation and/or mitigation of the potential negative effects. In view of the potential hazards from wrecks and historical wrecks, many countries have recently developed comprehensive risk assessment systems to examine the wrecks impacts in their national waters (Whittington et al, 2017).…”
Section: Impacts Of Shipwrecks On Hydrological Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Consoli et al (2015) reported that oil pollution is commonly resulted due to maritime accidents that significantly impacting marine environment and often portrayed by the media as environmental disasters with dire consequences predicted for the survival of marine flora and fauna, which therefore, mandatory for appropriate remediation and/or mitigation of the potential negative effects. In view of the potential hazards from wrecks and historical wrecks, many countries have recently developed comprehensive risk assessment systems to examine the wrecks impacts in their national waters (Whittington et al, 2017).…”
Section: Impacts Of Shipwrecks On Hydrological Featuresmentioning
confidence: 99%
“…There are over three million shipwrecks scattered on the ocean floor around the world (UNESCO, 2008), where 8 -9 thousands of wrecks on global scale are considered as potential sources of pollution, where approximately 2.5 -20.4 million tons of oil residual inside the wrecks (Michel et al, 2005). The navigational and environmental risks posed by shipwrecks present big challenges to maritime industry along several decades ago (Whittington et al, 2017).…”
Section: Introductionmentioning
confidence: 99%